PHENOMENON OF THE QUALITY OF EDUCATION IN MODERN SCIENTIFIC DISCOURSE - Batechko, Nina (Educological discourse, 2017)
The article highlights the peculiarities of grounding of the categories “quality” and “quality of education” in modern scientific discourse. At the same time, the concept of the “quality of education” is presented as a system object that combines the organizational structure, methods, processes and resources necessary for the functioning of the education system in order to meet its requirements, social norms and state educational structures. From the standpoint of openness, non-linearity, emergence, the concept of the quality of education is disclosed as a synergetic category. The interdisciplinary nature of the concept of the “quality of education” is pointed out. It should be noted that the synergy of the systemic and synergetic approaches can serve as a theoretical and methodological basis for the phenomenon under study. In the examined aspect, the present realities of introducing the basic principles of quality into the sphere of education of Ukraine are presented. The positioning of the quality of education as an open, non-linear system that is capable of self-organization will enable the development of progressive models for the development of the national system for ensuring the quality of education.